2015
DOI: 10.1117/12.2076333
|View full text |Cite
|
Sign up to set email alerts
|

Compact diode-pumped nanosecond Nd:YVO4grazing-incidence slab amplifier

Abstract: Abstract: A high average power and high beam quality nanosecond laser is presented that is based on CW diode side-pumped Nd:YVO 4 grazing-incidence slab amplifier. A TEM 00 , passively Q-switched diode-pumped Nd:YAG laser as the seed laser, generating a M 2 ≈1.3 beam train of 0.25W, 2.3ns pulses with adjustable repetition rate in the range 5-20kHz. After double-pass amplification, more than 20W of output power with a beam quality of M 2 ≈1.4 is obtained at an optical-optical efficiency of 35%. The high brightn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…For the wide absorption and large emission cross sections and proper fluorescence lifetime of Nd∶YVO 4 crystals, many diode-pumped Nd∶YVO 4 MOPA systems were reported [9][10][11][12][13][14][15][16] . Traditional diode end-pumped Nd∶YVO 4 straight amplifiers can be seeded by Nd∶YAG lasers or laser diodes (LDs) [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the wide absorption and large emission cross sections and proper fluorescence lifetime of Nd∶YVO 4 crystals, many diode-pumped Nd∶YVO 4 MOPA systems were reported [9][10][11][12][13][14][15][16] . Traditional diode end-pumped Nd∶YVO 4 straight amplifiers can be seeded by Nd∶YAG lasers or laser diodes (LDs) [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Traditional diode end-pumped Nd∶YVO 4 straight amplifiers can be seeded by Nd∶YAG lasers or laser diodes (LDs) [9][10][11] . Side-pumped Nd∶YVO 4 bounce amplifiers with grazing incidence beams have been proved to be an excellent design solution for achieving high gains, thus allowing for a significant power extraction with a compact and simple setup [12][13][14][15][16] . Agnesi et al reported a side-pumped Nd∶YVO 4 bounce amplifier, 1 MW pulse peak power with 577 ps duration and 545 μJ energy was achieved, and the average output power was 5.45 W at 10 kHz, corresponding to 13% extraction efficiency [14] .…”
Section: Introductionmentioning
confidence: 99%